Behavior, Attitudes, Food and Nutrition Practices in Pregnant Women - Jose Selva Suarez (International Journal of Science and Society, 2020)
The low food consumption, anemia and frequent infections during pregnancy are causes of maternal undernourishment; that’s why it is important to know attitudes and practices during pregnancy in order to design messages in favor of the nutrition for the pregnant woman. To have a basic line of knowledge, attitudes and practices of pregnant women from Ollantay (poor suburban area) that will allow us to make educative interventions. 156 surveys were applied, divided in 6 axes: (i) general data; (ii) knowledge about nutrition; (iii) nutritional attitudes; (iv) nutritional practices; (v) other foods; (vi) habits. The study was done in 2006. 86% knows that must drink milk, however only 35% drinks it everyday; 33%, two or three times per week and 27%, some times. 85% knows that they must take ferrous sulphate; 91% that they must consume 3 main meals and 1 snack. 59% knows what foods facilitate the absorption of iron and 47% which are rich in iron. Egg: the 44% consume it some times, the 38% two or three times per week and the 13%, every day. The 58% consumes barbecued chicken, the 30% hamburger, the 79% ice cream, the 56% cakes and candies, the 66% soda pops. Pregnant women know how many meals a day they must consume. The half knows which foods are iron rich and which facilitate its absorption. Iron rich foods are not of their affability. A high percentage has bad feeding habits. The high protein foods are little consumed by pregnant women.